Research on detection methods of related substances and degradation products of the antitumor drug selpercatinib - Jingjing Xiang; Liangliang Cai; Qin Wang; Yonghong Zhu; Yong Han (Frontiers in Chemistry)
BackgroundSelpercatinib, a selective RET kinase inhibitor, is approved for treating various cancers with RET gene mutations such as RET-rearranged thyroid cancer and non-small cell lung cancer. The presence of process-related and degradation impurities in its active pharmaceutical ingredient (API) can significantly affect its safety and effectiveness. However, research on detecting these impurities is limited.MethodsThis study developed and systematically validated a High-Performance Liquid Chromatography (HPLC) method for identifying selpercatinib and its related impurities. The method utilized a 4.6 mm × 250 mm chromatographic column with 5 μm particles, employing a flow rate of 1.0 mL/min, a detection wavelength of 235 nm, an injection volume of 10 μL, and a column temperature of 35°C. Mobile phase A was composed of a 9:1 ratio of water to acetonitrile, with the aqueous component adjusted to pH 2.5 and containing 2 mM potassium dihydrogen phosphate (KH2PO4) and 0.4% triethylamine. Mobile phase B was pure acetonitrile. The gradient elution program was as follows: 0–2 min, 5%B; 2–15 min, 5% to 15%B; 15–30 min, 15% to 35%B; 30–35 min, 35% to 45%B; 35–36 min, 45% to 5%B; 36–45 min, 5%B.ResultsThe chromatographic method established in this study was validated according to the ICH Q2 (R1) guidelines. The developed HPLC method demonstrated excellent specificity, sensitivity, stability, linearity, precision, accuracy, and robustness. It efficiently separated the impurities present in selpercatinib, thereby confirming the method’s efficacy in ensuring the purity and quality of the drug.ConclusionThe chromatographic method established in this study can be used for the detection of selpercatinib and its impurities, providing significant reference value for the quality research of selpercatinib bulk drug and its preparations, and ensuring the safety of medication for patients.